The role of ficolin as a pattern recognition receptor in antibacterial immunity in Eriocheir sinensis. Issue 128 (September 2022) - Zhao, Ke; Qin, Yukai; Nan, Xingyu; Zhou, Kaimin; Song, Yu; Li, Weiwei; Wang, Qun
Abstract: Ficolin, a member of the fibrinogen-related proteins family (FREPs), functions as a pattern recognition receptor (PRR) in vertebrates and in invertebrates as a novel lectin. In this study, we discovered the Ficolin homolog of Chinese mitten crab ( Eriocheir sinensis ), which we named Es Ficolin. The obtained sequence showed that it has a highly conserved C-terminal fibrinogen-related domain (FReD) and a coiled-coil structure for trimer formation. Es Ficolin was up-regulated in hemocytes after being stimulated by bacteria. Recombinant Es Ficolin protein binds to gram-negative and gram-positive bacteria and agglutinates bacteria through pathogen-associated molecular patterns. In-depth study found that recombinant Es Ficolin could effectively remove bacteria and showed direct antibacterial activity. Es Ficolin could also promote the phagocytosis of hemocytes to enhance bacterial clearance. These findings suggest that Es Ficolin plays an important role in the crab antibacterial immune response. Highlights: A Chinese mitten crab ficolin homolog, Es Ficolin, was identified. Es Ficolin was upregulated in hemocytes after bacterial infection. Es Ficolin binds and agglutinates bacteria via pathogen-associated molecular patterns. Es Ficolin showed direct antibacterial activity via hemocyte-induced phagocytosis. Es Ficolin has an important function in the crab antibacterial immune response.